Classification of Payment Patterns for Toyota Car Sales Using the Decision Tree Algorithm - Siregar, Martua Hami; Saiyar, Hafdiarsya; Desmulyati, Desmulyati; Noviansyah, Mohammad (Sean Institute, 2025)
Car sales represent a business sector highly dependent on the implementation of appropriate payment strategies to enhance customer satisfaction and operational efficiency. This study aims to classify payment patterns in Toyota car sales using the Decision Tree algorithm. Historical sales data were utilized to identify various attributes influencing payment methods, such as cash, credit, or leasing.Through processes of preprocessing, feature selection, and model training, the Decision Tree algorithm successfully established clear classification patterns based on variables such as payment type, gender, car type, and car category. The research findings indicate that the Decision Tree method not only provides a high level of accuracy in classifying payment patterns but also produces models that are easily interpretable by business decision-makers. Thus, the implementation of this classification technique is expected to assist companies in designing more effective and targeted sales and promotional strategies.